The Leadership Dilemma: Investigating the Relationship Between Leadership Style and Employee Performance - Krasniqi, Tringë; Drakulevski, LJubomir; Janeska iliev, Aleksandra (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
Background: Several research studies have been devoted to the relationship between leadership and employee performance. They provided significant results that leadership styles have a positive correlation with employee performance. Aim: The purpose of this paper is to examine how strong is correlation between leadership styles and employee performance in the private sector in Kosovo. This relationship between those variables has been little investigated by researchers in Kosovo, and from the research that we analyzed none of them take a laissez-faire style for research. We will consider three leadership styles: laissez-faire, transactional, and transformational leadership, along with employee performance, to provide the relationship between them. We will also discuss review papers that measured the correlation between these variables. Methods: A study was conducted to determine if there is a significant linear relationship between leadership style and employee performance. The research utilized Pearson’s Correlation and collected data through questionnaires distributed to employees and managers in various private-sector industries in Kosovo. A random sampling technique was used to collect 235 samples from the manufacturing, service, construction, and wholesale industries. The questionnaire was analyzed using Statistical Package for Social Sciences (SPSS) version 27. Yousef's (2000) scale was used to measure employee performance, while the Multifactor Leadership Questionnaire (Bass and Avolio 1995) was used to measure laissez-faire and transactional leadership, and transformational leadership was measured using a 7-item scale from Carless, Wearing, and Mann (2002). Results: According to the findings of the research, it has been confirmed that leadership styles have a low but positive correlation with employee performance. There is no statistically significant correlation between laissez-faire leadership and employee performance. Transactional leadership and transformational leadership have a low but positive correlation with employee performance. Also, the results show that most of the employees consider that personal performance is higher than their peers in the same kind of work around 5.88%.
Keywords: Leadership styles; laissez-faire; transactional; transformational; employee performance